Recent-onset and persistent tinnitus: Uncovering the differences in brain activities using resting-state functional magnetic resonance imaging technologies - Du, Haoliang; Feng, Xu; Qian, Xiaoyun; Zhang, Jian; Liu, Bin; Li, Ao; Huang, Zhichun; Gao, Xia (Frontiers in Neuroscience, 2022)
Objective: This study aimed to investigate the differences in intra-regional brain activity and inter-regional functional connectivity between patients with recent-onset tinnitus (ROT) and persistent tinnitus (PT) using resting-state functional magnetic resonance imaging (rs-fMRI), including the amplitude of low-frequency fluctuations (ALFF), regional homogeneity (ReHo), and voxel-wise functional connectivity (FC). Method: We acquired rs-fMRI scans from 82 patients (25 without recent-onset tinnitus, 28 with persistent tinnitus, and 29 healthy controls). Age, sex, and years of education were matched across the three groups. We performed ALFF, ReHo, and voxel-wise FC analyses for all patients. Results: Compared with the control group, participants with ROT and PT manifested significantly reduced ALFF and ReHo activity within the left and right dorsolateral superior frontal gyrus (SFG) and gyrus rectus (GR). Additional voxel-wise FC revealed decreased connectivity between the dorsolateral SFG (left and right) and the right superior parietal gyrus (SPG), right middle frontal gyrus (MFG), and left medial superior frontal gyrus (mSFG) within these two groups. Significant differences were observed between the ROT and PT groups, with the ROT group demonstrating reduced FC. Conclusion: Our data suggest that patients with PT have more difficulty monitoring external stimuli and reorienting attention than patients with ROT. In addition, patients who perceive higher levels of disruption from tinnitus are more likely to develop persistent and debilitating tinnitus once the tinnitus lasts longer than six months. Therefore, we strongly recommend that clinicians implement effective tinnitus management strategies in patients with ROT as soon as possible.